Comparing the impact of three pedagogy exercises for popularizing positive deviance concept among medical students in Bareilly: A quasi-experimental study using normal curve approach - Kumar, Ravi; Pareek, Shubham (Indian Journal of Community Health, 2024)
Background: There is usually an apprehension fear among medical student and doctors about use of statistics in their academic study. Objective: This study aim to compare the impact of three teaching methods to popularize the concept of positive deviance (PD) through Normal curve theory among medical student. Materials and Methods: This quasi-experimental study was conducted over two months. 149 first-year MBBS students were divided into three groups, receiving different interventions. Kruskal-Wallis H test and Paired t test applied to see the statistical significance of intervention. Results: A Total 149 students during post-intervention assessments showed significant improvements (p < 0.001) in knowledge scores across all groups, with the Positive deviance (PD) approach demonstrating the most gains (Cohen's d=12.671). Conclusions: This study conclude that the implementation of the normal curve along with PD as a conceptual framework proven to be a significant technique which highlights the effectiveness of using Normal curve and PD concepts to make statistics easy for medical students.